2017
DOI: 10.1097/olq.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Coverage and Utilization at a Sexually Transmitted Disease Clinic in a Medicaid Expansion State

Abstract: Background In Rhode Island, the Patient Protection and Affordable Care Act (ACA) has led to over 95% of the state’s population being insured. We evaluated insurance coverage and barriers to insurance use among patients presenting for services at the Rhode Island STD Clinic. Methods We analyzed factors associated with insurance coverage and utilization among patients presenting for STD services between July and December 2015. Results A total of 692 patients had insurance information available; of those, 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Yet, a previous analysis over 6 months at the same Rhode Island STD Clinic found that 30% of the total sample used insurance. 27 This is in line with the current analysis at the same clinic over a full year, which found that 28% of visits used insurance, which is well below the 73% that would be needed to break even if all visits were based on Medicaid. The previous study also showed that 22% of the total sample used private or other insurance 27 which is below the 38% of visits needed to break even at the private insurance rates, but exceeds the 11% of visits needed to break even at the list insurance rates.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Yet, a previous analysis over 6 months at the same Rhode Island STD Clinic found that 30% of the total sample used insurance. 27 This is in line with the current analysis at the same clinic over a full year, which found that 28% of visits used insurance, which is well below the 73% that would be needed to break even if all visits were based on Medicaid. The previous study also showed that 22% of the total sample used private or other insurance 27 which is below the 38% of visits needed to break even at the private insurance rates, but exceeds the 11% of visits needed to break even at the list insurance rates.…”
Section: Discussionsupporting
confidence: 87%
“…27 This is in line with the current analysis at the same clinic over a full year, which found that 28% of visits used insurance, which is well below the 73% that would be needed to break even if all visits were based on Medicaid. The previous study also showed that 22% of the total sample used private or other insurance 27 which is below the 38% of visits needed to break even at the private insurance rates, but exceeds the 11% of visits needed to break even at the list insurance rates. This makes the authors optimistic that a sufficient volume of visits would be reimbursed at an insurance rate that is higher than Medicaid and that would allow a clinic to be financially solvent.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The impact of expanded public health insurance programs is limited. Even with expansion of Medicaid funding to 95% of the adult population in Rhode Island, among patients seeking sexually transmitted infections testing and treatment, concerns about out-of-pocket expenses were still a barrier, especially for those who were unemployed (Montgomery et al, 2017). Individuals who had recently become insured in this study were more likely to be non-White minorities and of Hispanic/Latino(a) ethnicity and 26% of them obtained coverage under the Affordable Care Act.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple individual, interpersonal, community, and societal factors may impact access to health care, including appropriate STI screening, diagnoses, and treatment. The most common barriers to STI testing include lack of access to clinical services, out-of-pocket costs for both uninsured and underinsured, confidentiality concerns, and stigma associated with testing (Montgomery et al, 2017). These barriers may be more pronounced in racial and ethnic minorities with rates of chlamydia and gonorrhea highest in Black/African Americans in 2018.…”
mentioning
confidence: 99%